Peningkatan Motivasi Mantan Pecandu Narkoba Melalui Penerapan Punishment dan Reward Dalam Menjalankan Proses Pemulihan di Ipwl Yayasan Nazar - M.Rafli Muhajir; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The problems faced by drug residents are not far from the reduced level of motivation in carrying out the recovery process at the Rehabilitation Homes. This is partly due to the saturation factor that makes them bored in carrying out the recovery process. The target to be achieved is to increase the motivation of drug residents to stay enthusiastic, focus on carrying out rehabilitation and not get bored in carrying out the recovery process. Because if the saturation continues, it can cause his recovery to be disrupted. The solution offered in practicum 1 for individuals (Casework) is through the application of punishment and reward in helping the recovery process. The intervention program used in this practicum is the Micro Intervention by (Skidmore in Adi, 2013) which consists of; Engagement, Assessment, Planning, Plan Implementation, Evaluation and Termination.